Esophageal lichen planus: A case report and review of literature - Madhusudhan K; Sharma Raju (Wolters Kluwer Medknow Publications, 2008)
Lichen planus is a rare cause of esophagitis and esophageal stricture. It is invariably associated with oral mucosal involvement and the diagnosis has to be considered in such patients presenting with dysphagia. We present a case of esophageal stricture secondary to lichen planus.